Mineral-cement-emulsion mixtures (MCEM) modified with fine rubber - Kukiełka, Jerzy; Dębiński, Marcin (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
MCE mixtures fortified with fine rubber were the subject of research in laboratory tests in Lublin University of Technology. As a basic literature review shows, an amount of fine rubber in mixtures with cement in MCEM should be 2%, 4% and 6% of the aggregate. The mixtures were designed planned and prepared as samples for tests assessing the fulfillment of the requirements contained in the Manual [9]. Analysis of the results allows to assess the usefulness of fine rubber in MCE mixtures and is a basis for further detailed studies that are aimed at setting new quantitative requirements, going beyond the requirements included in the Manual.